Unusual Presentation of Systemic Lupus Erythematosus with Acute Pancreatitis: A Case Report : Life Sciences- Rheumatology - Alanazi, Majed Saleh; Hameed Alreshidi, Ahmed; Fahad Aldhamadi, Hamoud; Alrashidi, Yasir Saleh; Khalid Alshammari, Abdulaziz (International Journal of Life Science and Pharma Research, 2023)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease affecting any organ with diverse clinicalmanifestations. Lupus-related acute pancreatitis (AP) is a serious cause of SLE-induced acute abdominal discomfort, along with lupusmesenteric vasculitis. Systemic Lupus Erythematosus (SLE) is a complex and chronic autoimmune disease characterized by its ability toaffect virtually any organ system, resulting in a wide array of clinical manifestations. One particularly severe complication associatedwith SLE is lupus-related acute pancreatitis (AP), which can cause acute abdominal discomfort. Lupus mesenteric vasculitis is anotherabdominal manifestation of SLE, further highlighting the systemic nature of the disease. Lupus pancreatitis is more common in femalesand the third decade of life, with an incidence ranging from 0.7% to 4%. This case report describes a 16-year-old Saudi female whopresented to the emergency department with episodic fever, epigastric abdominal pain, sweating, loss of appetite, and diarrhoea,among other symptoms. Her laboratory test results showed leukopenia, anaemia, increased liver, and pancreatic enzyme levels,increased inflammatory markers, and hypocomplementemia. She was diagnosed with lupus pancreatitis after ruling out other potentialcauses. Treatment included steroids and hydroxychloroquine. The patient showed marked improvement in resolving all symptoms,emphasizing the need for prompt diagnosis and management. This case insists on timely diagnosis and appropriate management inmitigating the potentially severe consequences of lupus pancreatitis and other SLE-related complications. In conclusion, SLE is amultifaceted autoimmune condition that affects various organs, including the pancreas, leading to conditions like lupus pancreatitis.The presented case serves as a poignant reminder of the diverse clinical presentations of SLE and highlights the crucial role of promptdiagnosis and effective management in improving patient outcomes.